2016
DOI: 10.21823/2311-2905-2016-0-1-108-116
|View full text |Cite
|
Sign up to set email alerts
|

Using Custom Triflange Implant in Revision Hip Arthroplasty in Patient With Pelvic Discontinuity (Case Report)

Abstract: Revision hip arthroplasty rate is growing, and pelvic discontinuity rate ranges from 1% to 5% of acetabular component revision reasons. According to AAOS acetabular defects classification, pelvic discontinuity is fourth type defect in which cranial part of hip bone is separated from caudal part at acetabular level. Usually it occurs from bone loss secondary to osteolysis, infection, fracture or aseptic loosening. There are a lot of techniques for pelvis discontinuity treatment. Published results of bulk allogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…In these cases, 3DP customized triflange acetabular component (CTAC) was implanted into bone defect precisely, and all implants showed reliable fixation in the ischium, pubis and ilium. 173 Other researchers also implanted 3DP CTAC into pelvic discontinuity, and found that there were improved HHS score without complications. 174 This technique is a reliable and promising option in these cases.…”
Section: Application Of 3dp Metallic Implants In Orthopedicsmentioning
confidence: 99%
“…In these cases, 3DP customized triflange acetabular component (CTAC) was implanted into bone defect precisely, and all implants showed reliable fixation in the ischium, pubis and ilium. 173 Other researchers also implanted 3DP CTAC into pelvic discontinuity, and found that there were improved HHS score without complications. 174 This technique is a reliable and promising option in these cases.…”
Section: Application Of 3dp Metallic Implants In Orthopedicsmentioning
confidence: 99%
“…In such cases, it is hard to provide reliable fixation of the acetabular component because of limited contact surface with host bone and movement of bone fragments. In an aseptic loosening of the acetabular component and pelvic discontinuity case, 3DP customized triflange acetabular component (CTAC) fit the bone defect precisely and provided reliable fixation in the ischium, pubis and ilium (Tikhilov et al , 2016). Kavalersky et al also used 3DP CTAC in pelvic discontinuity, and no complications were found and HHS scores were significant improved (Kavalersky et al , 2016).…”
Section: Application Of Three-dimensional Printed Metal Implants In the Field Of Orthopedicsmentioning
confidence: 99%
“…Ивк для реконструкции значительных дефектов вертлужной области на сегодняшний день не являются революционным методом лечения [15][16][17][18][19][20]. однако в нашей стране первая подобная операция была выполнена менее трех лет назад [22]. Целый ряд вопросов требует дальнейшего освещения как в отечественной, так и в зарубежной литературе.…”
Section: Introductionunclassified